NT‐proBNP and cardiac troponin I concentrations in dogs with tick paralysis caused by Ixodes holocyclus. Issue 8 (August 2016) - Nicolson, GP; McGrath, ALH; Webster, RA; Li, J; Kaye, S; Malik, R; Beijerink, NJ
Abstract : Objective: The purpose of this study was to determine through measurement of cardiac biomarkers whether there was cardiac involvement in dogs infested with Ixodes holocyclus . Methods: Dogs with tick paralysis and no–mild (group 1; n = 44) or moderate–severe respiratory compromise (group 2; n = 36) and a control group of dogs (n = 31) were enrolled. Plasma N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), serum cardiac troponin I (cTnI) and serum creatinine concentrations were determined. For most of the affected dogs SpO2 was determined. Results: SpO2 readings did not differ between groups 1 and 2. Three animals in group 2 had an SpO2 reading <90%. NT‐proBNP concentrations were lower in both groups 1 and 2 compared with the control group. There was no difference in cTnI concentrations among groups, although they were elevated in four dogs, including the three dogs in group 2 with SpO2 readings <90%. Creatinine concentrations were within the reference interval for all dogs, but did differ among the groups, with control dogs having the highest values, followed by group 1 and then group 2. Conclusion: This study did not detect significant cardiac involvement in dogs with tick paralysis induced by I. holocyclus . Evidence for reduced preload in dogs with tick paralysis was provided by lower NT‐proBNP concentrations compared with control dogs. Severe hypoxaemia may not be a significant component of the clinical picture in many of the dogs presenting with tick paralysis. Dogs with severe hypoxaemia may have loss of cardiomyocyte integrity, reflected by elevated cTnI concentrations.